Assessment of phenotypic performance, association and path analysis of upland cotton (Gossypium hirsutum L.) yield and fiber quality traits in central Sudan - Ahmed, Hassan; Ibrahim, Sief Eldin; Ibrahim, Abu Elhassan; Suliman, Abbas (Gezira Journal of Agricultural Science; Vol 17 No 1 (2019), 2019)
Fifteen upland cotton inbred lines and the check (commercial cultivar Hamid ) were evaluated during 2013/14 and 2014/15 seasons at the Rahad Research Station Farm, Gezira Research Station Farm and Sennar Research Station Farm of the Agricultural Research Corporation, Sudan. The objective was to estimate seed cotton yield potential and carry out interrelationships and path coefficient analysis. Treatments were arranged in a randomized complete block design with four replicates. Data were collected on days to 50% flowering, number of sympodia/plant, number of bolls / plant, plant height, ginning out-trun, boll weight, seed cotton yield (kg/ha) and fiber characteristics . The study showed significant differences among the genotypes for all characters. Seed cotton yield over environments ranged between 1907 and 2380kg/ha. The genotypes R-6, R-40, R-231 and R-43 showed the best seed cotton yield ranging from 2310 to 2380 kg/ha over environments. At the same time, these genotypes had good number of sympodia / plant, GOT%, lint index, seed index and number of bolls / plant. Over environments, line R-231 revealed high fiber length (28.9 )2.5% SL() and bundle strength (30 g∕tex). The simple linear correlation and path coefficient analysis showed that seed cotton yield was highly significantly and positively correlated with most traits. In conclusion, genotypes R-6, R-40, R-231, and R-43 are recommended for further testing over a range of environments to examine their yield and fiber quality for large field production.   تم اختبار 15 سلالة نقية من القطن الأكالا ( Gossypium hirsutum L.)  بالأضافة الي الصنف حامد المنزرع تجاريا بالسودان في موسمي 14/2013  و 15/2014 في محطة بحوث الرهد و محطة بحوث الجزيرة و محطة بحوث سنار, هيئة البحوث الزراعية , السودان. الهدف من هذه التجربة هو تقدير الاداء والعلاقات المتداخلة للانتاجية ومكوناتها.  استخدم تصميم القطاعات العشوائية الكاملة بأربعة مكررات. الصفات التي تم قياسها هي %50 ازهار و عدد الأفرع الثمرية بالنبات و عدد اللوز بالنبات و طول النبات و تصافي الحليج و وزن اللوزة والانتاجية بالهكتار وخصائص الشعرة. نتائج التحليل أظهرت فروقات معنوية بين الطرز الوراثية في جميع الصفات. متوسط الانتاجية تراوح ما بين 1907 و 2380 كيلو جرام للهكتار. أظهرت الطرز الوراثية التالية:  R-6و  R-40و R-231  و R-43 انتاجية عالية تراوحت ما بين 2310 الي 2380 كيلوجرام للهكتار كمتوسط لكل البيئات. امتازت هذه الطرز بأفرع ثمرية كثيرة و بتصافي حليج عالي و عدد كبير للوز بالنبات. أظهرت السلالة R-231 طول شعرة (28,9) 2,5% SL ومتانة الفتلة (30 g∕tex) في البيئات المختلفة. كما أظهر تحليل المسار والارتباط الجيني أن كل الصفات ارتبطت ايجابا بانتاجية القطن زهرة مع تصافي حليج عالي. خلاصة البحث واستناداً علي متوسط الأداء يوصى باختبار انتاجية الطرز الوراثية R-6 وR-40 و R-231و R-43   في عدة مواقع ومواسم للتأكد من نتائج هذه الدراسة والاستفادة منها في توصية باجازة بعض هذه الطرز لتناسب الظروف البيئية في السودان.